Risk factors for patients hospitalized with recurrent colon diverticular bleeding: a single center experience - You, Hye-Su; Kim, Dong Hyun; Cho, Seo-Yeon; Park, Seon-Young; Park, Chang Hwan; Kim, Hyun-Soo; Choi, Sung Kyu (Frontiers in Medicine, 2023)
Background/aims Colonic diverticular bleeding (CDB) is a common cause of acute lower gastrointestinal bleeding. Patients with CDB are at increased risk for recurrence. Here, we aimed to evaluate the clinical course of patients with CDB and identify risk factors for recurrent CDB (rCDB). Methods We included patients who were hospitalized at a single tertiary center for management of CDB between January 2005 and March 2020. A Cox proportional hazards regression analysis was performed to evaluate the risk factors of patients with rCDB as follows: model 1 adjusted by age, Charlson comorbidity index (CCI), and presence of bilateral colon diverticula; model 2 adjusted by age, CCI, and presence of left side colon diverticula; model 3 adjusted by age, CCI, and presence of sigmoid colon diverticula. Results Among 219 patients (mean age, 68.0 years; 55 females), 56 and 163 had definite and presumptive CDB, respectively. During the median period of 506 days, 62 patients (28.3%) experienced rCDB. CCI score ≥ 4 was independently associated with rCDB in models 1, 2 and 3 (all p < 0.05). Age ≥ 75 years was independently associated with rCDB in models 1 and 2 (both p < 0.05). The presence of bilateral colon and sigmoid colon diverticula were independently associated with rCDB in models 1 and 3, respectively (both p < 0.05). Conclusion rCDB frequently occurred at any time in patients with previous CDB. High CCI scores and distribution of colon diverticula were associated with rCDB. Clinicians should consider a possible rCDB for a patient considering age, comorbidity, and distribution of colon diverticula.